Video ministry : using media in worship without going Hollywood - Stella, Constance E. (Nashville, TN : Abingdon Press, 2006)
"Accompanying DVD-ROM contains video and PDFs. cf. opening frames."--From source other than the Library of Congress
Introduction -- Purpose -- Forming ministry on purpose -- Applying purpose in your ministry's work -- Applying purpose in the formation and operation of your ministry -- Questions for media ministry planning -- Values -- Working within your values -- Applying values in your ministry's work -- Applying values in the formation and operation of your ministry -- Questions for media ministry planning -- Culture -- Reflecting your congregation's culture -- Applying culture in your ministry's work -- Applying culture in the formation and operation of your ministry -- Questions for media ministry planning -- Vision -- Working toward vision -- Applying vision in your ministry's work -- Applying vision in the formation and operation of your ministry -- Whose idea is it, anyway? -- Final word on vision -- Questions for media ministry planning -- Excellence -- Worshiping with excellence -- An excellent journey -- An excellent exercise -- Setting boundaries -- Defining excellence for your ministry -- Excellent execution -- An almost-sacred rule -- Applying excellence in the formulation and operation of your ministry -- Story one and two -- Questions for media ministry planning -- Meaning -- Introduction : defining the principle of meaning -- Applying meaning in your ministry's work -- Applying meaning in the formulation and operation of your ministry -- A final thought about meaning -- Questions for media ministry planning.
Keywords: Public worship -- Audio-visual aids